Tingkat Rasa Percaya Diri Mahasiswa Prodi Manajemen Informasi Kesehatan Dalam Perkuliahan Biostatistik - Urim Gabriel Dinasti Laowo; Ita Monita Munthe (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Self-confidence is a personality of confidence in one's own abilities in lectures so that it is not easily influenced by others. Self-confidence is one of the aspects that must be possessed by students in the lecture  process.The purpose of this study is to explore information related to how the level of confidence of STIKes Santa Elisabeth Medan   Health Information Management students in biostatistics owned by students.In this study, there are two aspects of self-confidence that are measured ,namely confidence in  completing tasks, and confidence in learning.This research uses a quantitative approach  using correlation analysis. The population used is all students of the Level 1 Health Information Management Study Program,STIKes Santa Elisabeth Medan with a total of  18 people.The sampling technique used is stratified random sampling.Student self-confidence data is collected through student self-confidence questionnaires.The results of the study on the level of student confidence in completing assignments obtained  there were  6 people (33.3%) who had high  self-confidence , there were 8 people (44.4%) who had a sense of enough confidence and there are 4 people (22.22%) who have less self-confidence. Students of  the Health Information Management Study  Program level 1 have a lack of  confidence because there are some students who lack  the intention to study and assumes that the material of the biostatistics course is very difficult to  understand. It is recommended  to students to be serious in learning and increase self-confidence to ask about things that are still not understood because the more questions there will be more and more questions the more knowledge we get.